Landscape changes in Norwegian mountains: Increased and decreased accessibility, and their driving forces. (July 2016) - Eiter, Sebastian; Potthoff, Kerstin
Highlights: Changes in accessibility are a crucial landscape change for land use development. Changes in accessibility lead to a concentration of activities. Driving forces initiate or influence changes in accessibility. Counterforces and retarding effects of driving forces need to be considered. Local-scale drivers can outplay the strong impact of broad-scale drivers. Abstract: Accessibility is a central issue for human activity, particularly in mountain areas. We investigate changes in physical accessibility in a Western Norwegian mountain area during the past 40–60 years and identify driving forces of changes. Changes in accessibility were measured as changes in travel time between permanently and seasonally inhabited farmsteads. Additionally, travel time from new access points in the mountains was calculated. C.75% of the investigated access routes to seasonal farmsteads have remained unchanged due to continued use or maintenance work, or been slightly improved due to development of paths into roads. In addition, new access routes have emerged as a result of road construction. Regrowth of paths due to abandonment of seasonal farming has reduced accessibility. Changes in accessibility have led to a concentration of activities in more easily accessibly parts of the study area. Documented changes in accessibility result from a complex interaction of driving forces that initiate or influence change. Important drivers interacting with road construction and abandonment of seasonal farming can be categorized as socio-economic, political and technological. However, the importance of culturally rooted commitment of local people or a small number of enthusiasts must not be underestimated.